2022
DOI: 10.1186/s12891-021-04934-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-year clinical and economic burden, risk and outcomes following application of software-assisted hexapod ring fixation systems

Abstract: Background Multiplanar external fixation systems that employ software-assisted deformity correction consist of rings connected by angled struts, defined as hexapod ring fixators (HRF). Costs and outcomes associated with the application of HRFs are not well documented. This study was designed to provide a nationwide baseline understanding of the clinical presentation, risks, outcomes and payer costs, and healthcare resource utilization (HCU) of patients requiring application of an HRF, from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…A 2022 analysis of the burden of care following index hexapod application showed an average $35,986.88 (range $27,363.52-$52,546.37) spent in the 12-months following post-index surgery for those aged <17 with congenital deformity. Reid, et al, found this group of 168 patients, with an average duration of care similar to ours at 149.5 days, also had an average 22.26 outpatient physical therapy appointments and average 8.94 outpatient imaging procedure [14].…”
Section: Discussionsupporting
confidence: 78%
“…A 2022 analysis of the burden of care following index hexapod application showed an average $35,986.88 (range $27,363.52-$52,546.37) spent in the 12-months following post-index surgery for those aged <17 with congenital deformity. Reid, et al, found this group of 168 patients, with an average duration of care similar to ours at 149.5 days, also had an average 22.26 outpatient physical therapy appointments and average 8.94 outpatient imaging procedure [14].…”
Section: Discussionsupporting
confidence: 78%
“…In this narrow, perioperative time period, patients with deep infection with nonunions were not different from patients with deep infection without nonunions, when analyzing adjusted means for costs or complications; however, in our second manuscript looking at the 2-year post-index period, patients with deep infection and nonunion did have greater post-operative care requirements and complication risks in the time frame from day after surgery to two years post-index [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study focuses on the intra-operative period when HRF systems are first applied to the patient (defined herein as the “index”), and is designed to describe the pathology, diagnosis, comorbidities, complications, costs, healthcare utilization and hospital discharge disposition of patients with HRF application during these early intraoperative time points. The post-operative outcomes, from index to 2-year post-application, are described in a separate publication [ 23 ].…”
Section: Introductionmentioning
confidence: 99%